2009
DOI: 10.1007/s00439-009-0753-3
|View full text |Cite
|
Sign up to set email alerts
|

Malaria severity and human nitric oxide synthase type 2 (NOS2) promoter haplotypes

Abstract: Nitric oxide (NO) mediates host resistance to severe malaria and other infectious diseases. NO production and mononuclear cell expression of the NO producing enzyme-inducible nitric oxide synthase (NOS2) have been associated with protection from severe falciparum malaria. The purpose of this study was to identify single nucleotide polymorphisms (SNPs) and haplotypes in the NOS2 promoter, to identify associations of these haplotypes with malaria severity and to test the effects of these polymorphisms on promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…Authors conclude that this causeeffect relationship might be more complex than previously thought (Levesque et al, 2010).…”
Section: Nitric Oxide Synthase 2 (Nos2) Promoter Polymorphismmentioning
confidence: 81%
“…Authors conclude that this causeeffect relationship might be more complex than previously thought (Levesque et al, 2010).…”
Section: Nitric Oxide Synthase 2 (Nos2) Promoter Polymorphismmentioning
confidence: 81%
“…NOSII large (CCTTT) n microsatellite repeats are associated with protection from disease manifestation Genotyping of the microsatellite repeat in the promoter of NOSII revealed the presence of ten alleles, (CCTTT) [7][8][9][10][11][12][13][14][15][16][17] , in both the endemic and non-endemic regions. The frequency of each microsatellite allele in the control and patient groups is shown in Fig.…”
Section: Association Of Thbs1 Polymorphisms With Susceptibility To Famentioning
confidence: 99%
“…4a, b. (CCTTT) 12 was the predominant allele in the controls of both regions. We, thus, categorized the repeats into small repeats of ≤12 (SR, CCTTT 7-12 ) and large repeats of ≥13 (LR, CCTTT [13][14][15][16][17] to analyze the association of the repeat polymorphism with disease susceptibility/resistance. Large repeats CCTTT 13-17 exhibited association with protection from disease manifestation in both the endemic (p < 1 × 10 −5 ) and non-endemic regions (p<1×10 −3 ) (Fig.…”
Section: Association Of Thbs1 Polymorphisms With Susceptibility To Famentioning
confidence: 99%
See 1 more Smart Citation
“…The NOS2 gene codes for the inducible nitric oxide synthase (iNOS) that is responsible for high-level production of NO by activated phagocytes (4). Several studies focused on NOS2 promoter polymorphisms have reported genetic association to different malaria clinical outcomes (5)(6)(7)(8)(9)(10)(11)(12), but the role of such variants in malaria infection progression and nitric oxide production appears to be complex (13). Moreover, it is unclear whether NOS2 genetic variants play a role in susceptibility to asymptomatic malaria (14,15).…”
mentioning
confidence: 99%